The impact of moderate to severe osteoarthritis on the physical performance and quality of life: a cross-sectional study in Greek patients (PONOS study) - P. Savvari; I. Skiadas; S. A. Papadakis; V. Psychogios; O. D. Argyropoulou; A. P. Pastroudis; G. A. Skarpas; A. Tsoutsanis; A. Garofalakis; G. Katsifis; D. Boumpas; D. Menegas (BMC Musculoskeletal Disorders, 2023)
Abstract Background Osteoarthritis (OA) represents a leading cause of disability with limited data available for the Greek patients. Objectives To evaluate the impact of moderate to severe symptomatic hip/knee OA under treatment on physical performance and quality of life. Methods A non-interventional, cross-sectional, epidemiological study of patients with moderate/severe OA, recruited in a single visit from 9 expert sites in Athens, Greece. Assessments were based on commonly used outcome scales: the Hip disability and Osteoarthritis Outcome Score (HOOS), the Knee Injury and Osteoarthritis Outcome Score (KOOS) and the EuroQol-5-Dimensions 3-levels questionnaire (EQ-5D-3L). Results One hundred sixty-four patients were included in the analysis. Most of the patients were females (78.7%), with a mean age of 70.5 ± 10.2 years. Comorbidities were reported by 87.2% of patients with hypertension being the most frequently reported (53.7%), followed by dyslipidemia (31.1%), obesity (24.4%) and diabetes mellitus (23.2%). Paracetamol was the most common treatment (96%), followed by NSAIDs (75%), opioids (50%) and locally applied medications (42.7%). Both hip and knee OA patients showed substantial deterioration in health-related quality of life (QoL) and health status as reflected by the HOOS/KOOS (Function in sport and recreation was the most impaired subscale, followed by Hip- or Knee-related QoL). The mean EQ-5D-3L index score was 0.396 ± 0.319 and the mean EQ-VAS score was 52.1 ± 1.9. When compared indirectly to the local population norms our OA population had worse QoL indices. Conclusion Our findings suggest the functional disability and impaired QoL of Greek patients with moderate/severe hip/knee OA under treatment emphasizing the need for novel treatments that will reduce the burden of the disease.